Effect of Isokinetic Training on Quadriceps Muscle Strength in Osteoarthritis of Knee - Naresh Bhaskar, Raj; Soumendra, Saha; Amran, Shokri (2018)
Pressure Ulcer (PU) is a common health problem particularly among the physically limited or bedridden and the group most vulnerable to suffer this condition is the frail elderly. The Objective was to determine the efficacy of using the Cavilon cream plus the PU prevention intervention in reducing the progress of PU development among Geriatric inpatient in both groups. Using the Quasi experimental study design, where the participants were divided into two groups. The test group received the Durable barrier cream (Cavilon cream) plus the pressure ulcer prevention intervention as per protocols which linked to Braden risk score (AHCPR 1992 pressure ulcer protocol prevention) whilst the control group received the pressure ulcer prevention intervention as per protocols linked to Braden risk score only. Independent t-test were conducted, the mean different between test and control group was 4.02 and the standard deviation different between test and control group 0.5. The p value for the equality mean is 0.00, which is less than 0.05, 95% CI (2.72 – 5.31), which did not include 0, therefore there is a significant different in the change score between test and control group. The change in test group is much higher compare to control group